Research on family and human development in Stricto Sensu disciplines (Research, Society and Development, 2023)
This article aims to contribute to the teaching of psychology by reporting an experience, conducted by two psychologists over a period of 15 years, in a interdisciplinary postgraduate program. It is an experience report. In a regular discipline of the Stricto Sensu, research was carried out in collaboration with the students enrolled in it during each of the fifteen periods in which it was taught, resulting in scientific productions published in congresses and scientific publications by both students and professors. This article details the procedure adopted to carry out the collaborative research, as well as the products derived from it.